Transurethral resection versus open bladder cuff excision in patients undergoing nephroureterectomy for upper urinary tract carcinoma: Operative and oncological results - Charalampos Fragkoulis (Taylor & Francis Group, 2017)
Objectives: To evaluate the impact of distal ureter management on oncological results after open nephroureterectomy (ONU) comparing transurethral resection of the intramural ureter to conventional open excision, as controversy still exists about the method of choice for managing the distal ureter and bladder cuff during ONU. Patients and methods: We retrospectively collected data from 378 patients who underwent ONU for upper urinary tract transitional cell carcinoma (UUT-TCC) from 1988 to 2009. Patients were divided into two subgroups according to the type of operation performed. Group A comprised 192 patients who had ONU with open resection of the bladder cuff from 1988 to 1997. Group B comprised 186 patients in whom transurethral resection of the intramural ureter plus single incision ONU was performed between 1998 and 2009. The mean operative time, hospital stay, duration of catheterisation, bladder recurrence rates, and cancer-specific survival (CSS) were assessed. Results: The total operative time was statistically significantly less in the endoscopic group (Group B). For catheterisation, patients treated with an open approach (Group A) had a statistically significantly shorter duration of postoperative catheterisation. There was no statistical difference between Groups A and B for the bladder recurrence rate (Group A 24% vs 27% in Group B, P = 0.51). There was no difference in CSS at the 5-year follow-up. Conclusions: ONU with transurethral resection of the intramural ureter up to the extravesical fat followed by ureter extraction is an oncologically safe and technically feasible operation.